Neighborhood of fear : the suburban crisis in American Culture, 1975-2001 - Riismandel, Kyle, 1978- (Baltimore : Johns Hopkins University Press, 2020)
"This is a work of American history and cultural studies in which the author examines how Americans imagined and regulated suburban space in the last quarter of the twentieth century. Beginning in the 1970s, rising crime, environmental threats, and conflicts over the use of public space made suburbanites feel threatened. And the technologies of cable television, VCRs, and video games brought representations of these threats into suburban homes. The author interprets how suburbanites responded to these perceived threats through a strategy of "productive victimization" to protect their communities"--
Age of the NIMBY : environmental hazard and spatial power on the suburban landscape -- The neighborhood of fear : toxic suburbia, affective practice, and the invisible prison -- "Fear stalks the streets" : home security, kidnapping, and the making of the carceral suburb -- Punks, mallrats, and out-of-control teenagers : production and regulation of suburban public space -- Parental advisory -- explicit content : popular culture and (re)possessing the suburban home.
Includes bibliographical references and index.
Keywords: Suburbs -- United States -- History -- 20th century; Suburban life -- United States -- History -- 20th century; Suburbanites -- Political activity -- United States; Suburbs -- Environmental aspects -- United States; Fear -- Political aspects -- United States; Privilege (Social psychology) -- United States; Social values -- Political aspects -- United States; United States -- Civilization -- 20th century